Evaluation of a novel esophageal retractor utilizing vacuum suction and mechanical force for deviating the esophagus. (15th May 2020) - Houmsse, Mahmoud; Daoud, Emile G.; Joseph, Matthew; Weiss, Raul; Essandoh, Michael
Abstract: Background: Deviation of the esophagus prevents esophageal injury during atrial fibrillation ablation. Objectives: This study is to evaluate, in animals, safety and effectiveness of a novel esophageal retractor that utilizes vacuum suction and mechanical force to deviate the esophagus. Methods: Following general anesthesia, a radiopaque ruler was placed behind the animal perpendicular to the esophagus. The esophageal retractor was inserted and esophagram was completed. Suction force (280‐300 mm Hg) was applied to the distal aspect of the device that resulted in adherence of the esophagus in a circumferential manner. Then movement of a deflecting arm was used to deviate the esophagus. Four animal studies completed: (a) deviation distance and presence of trailing edge; (b) effect of 1 hour continuous suction and deviation upon esophageal cellular architecture; (c) impact on luminal esophageal temperature (LET) during high power ablation; and (d) compatibility of esophageal retractor with electroanatomic mapping system. Results: The distance of deviation to the right (26.6 ± 2.5 mm) was higher than to the left (18.7 ± 2.3 mm;  P  < .01). There was no esophageal trailing edge in 65/68 deviations (96%). With continuous suction for 1 hour, pathology revealed small, <1mm, circular area of hyperemia in the esophageal mucosa. During high power ablation, the maximum increase in LET was 0.2°C. Finally, there was no interference between the device and electro‐anatomical mapping system. Conclusion: In animal models, the esophageal retractor utilizing vacuum suction was successful at deviating the esophagus without significant trailing edge and with minor (1 mm) injury with prolonged continuous suction.